Comparison between refraction measured by Spot Vision ScreeningTM and subjective clinical refractometry (Clinics, 2016)
OBJECTIVE: The purpose of this study was to evaluate the accuracy of Spot Vision ScreeningTM as an autorefractor by comparing refraction measurements to subjective clinical refractometry results in children and adult patients. METHODS: One-hundred and thirty-four eyes of 134 patients were submitted to refractometry by Spot and clinical refractometry under cycloplegia. Patients, students, physicians, staff and children of staff from the Hospital das Clínicas (School of Medicine, University of São Paulo) aged 7-50 years without signs of ocular disease were examined. Only right-eye refraction data were analyzed. The findings were converted in magnitude vectors for analysis. RESULTS: The difference between Spot Vision ScreeningTM and subjective clinical refractometry expressed in spherical equivalents was +0.66±0.56 diopters (D), +0.16±0.27 D for the vector projected on the 90 axis and +0.02±0.15 D for the oblique vector. CONCLUSIONS: Despite the statistical significance of the difference between the two methods, we consider the difference non-relevant in a clinical setting, supporting the use of Spot Vision ScreeningTM as an ancillary method for estimating refraction.